Introduction: New Directions in Clinical Legal Education—Law for the People - Peter A. Joy (Washington University Journal of Law & Policy, 2008)
The essays in this special volume of the Washington University Journal of Law & Policy represent a range of approaches for teaching and practicing law, but they have one thing in common. In each instance, the authors promote a vision of legal education and the practice of law that stresses access to justice for individuals and communities traditionally unrepresented or underrepresented by the legal profession. For those contributors writing about law school teaching, their emphasis on access to justice seeks to prepare law students to become ethical, effective lawyers who will strive to promote justice and fairness through the practice of law. For those writing about specific practice areas or types of law practice, they outline more effective strategies for serving clients and providing them with access to justice. Together, these Essays reflect the authors’ shared commitment to give meaning to the lawyer’s ethical obligation to bear “special responsibility for the quality of justice.”
Keywords: Clinical legal education; Legal education – innovative approaches; Discrimination; Access to justice; Professional ethics; Legal profession; Lawyering; Community lawyering; International; United States; Clients